Prototype Pengeringan Cengkeh Dengan Menerapkan IoT Yang Berbasis Android - Pratama, Ade; Sulaksono, Danang Haryo (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
Clove is a kind of spice used in various industries, such as clove cigarettes, pharmaceuticals, cosmetics, and spices. During the rainy season, the supply of dry cloves ready for sale becomes scarce because it is difficult to dry wet cloves. Therefore, the drying prototype was designed to use a heater for the clove drying process. IoT (Internet of Things) can be implemented to take advantage of better and more flexible time estimation This research designed a clove dryer using an Android application as a control application. The tool for drying cloves can be connected to the internet for monitoring and controlling the process from an Android smartphone. The system employed the ESP32 as a microcontroller, a capacitive sensor, DHT22 as the sensor input data for drying parameters, and a heater with 400 watts of power. Testing the drying process is carried out according to the value limit of each sensor and the time limit set by the Android application. The research results indicated that every 500 grams of wet cloves with a drying temperature of 74°C–77°C and a drying process time of 3 hours 35 minutes would produce 200 grams of dry cloves with a moisture content of 14%. The results of measuring network quality with the TIPHON standard obtained an average index value of 3.75 in the satisfactory category